Monitoring the South-South cooperation (October 2015-April 2016) - Surasky, Javier (Revista Española de Desarrollo y Cooperación, 2023)
South-South Cooperation is starting to face the challenges related to the implementation of the 2030 Agenda. However, different regions behave differently, making it difficult to maintain a leading role on the global stage.
Keywords: South-South Cooperation; 2030 Agenda; America; Africa; Asia